Clinical observation of Traditional Chinese Medicine collapse stains combined with wax therapy in the treatment of urinary dysfunction in patients with multiple system atrophy (中药塌渍联合蜡疗治疗多系统萎缩患者排尿障碍临床观察与护理) - GAO Bo (高波); CHEN Hong (陈宏) (中西医结合护理, 2024)
Objective To explore the clinical effect of Traditional Chinese Medicine collapse stains combined with wax therapy in the treatment of urinary dysfunction in patients with multiple system atrophy. Methods A total of 30 patients with multiple system atrophy accompanied by urinary dysfunction were divided into observation group and control group according to the time sequence of hospital admission, with 15 cases in each group. The control group received routine treatment and nursing, and the observation group was treated with Traditional Chinese Medicine collapse stains combined with wax therapy based on the control group. The therapeutic effect of the two groups was compared by using Overactive Bladder Symptom Score (OABSS). Results The total score of OABSS was decreased in both two group after treatment, and OABSS score in the observation group was lower than that in the control group(P＜0. 05). Conclusion Traditional Chinese Medicine collapse stains combined with wax therapy can effectively relieve urinary dysfunction and improve the quality of life of the patient with multiple system atrophy, and it is worth promoting. (目的 探讨中药塌渍联合蜡疗治疗多系统萎缩患者排尿障碍的效果, 总结护理体会。方法 选取2023年1月—8月科室收治的30例多系统萎缩伴排尿障碍患者为研究对象, 根据入院时间顺序分为观察组和对照组, 各15例。对照组给予常规治疗及护理, 观察组在对照组的基础上增加中药塌渍联合蜡疗治疗。采用膀胱过度活动症状评分(OABSS)进行疗效评估。结果 治疗后两组患者OABSS总分较治疗前降低(P＜0. 05), 且观察组OABSS总分低于对照组(P＜0. 05)。结论 中药塌渍联合蜡疗可进一步改善多系统萎缩患者排尿障碍, 有助于提升患者的生活质量。)